ChemInform Abstract: New Xanthones from Garcinia bracteata and Their Cytotoxicities. Issue 35 (8th August 2013) - Hu, Qiufen; Niu, Deyun; Li, Xiangli; Qin, Yunhua; Yang, Zongyan; Zhao, Guoli; Yang, Zhongxiu; Gao, Xuemei; Chen, Zhangyu
Abstract Two new xanthones, bracthone A (Ia) and B (Ib), are isolated from the stems of Garcinia bracteata together with four known xanthones.